SOSIALISASI POTENSI ENERGI TERBARUKAN ANGIN (BAYU) ANTARA UNIVERSITAS MATARAM (UNRAM) BEKERSAMA DENGAN UVERSITAS TEKNOLOGI SUMBAWA (UTS) DI PULAU SUMBAWA - Made Sutha Yadnya; Teti Zubaidah; Abdullah Zainuddin; Bulkis Kanata; Paniran Paniran (Jurnal Gema Ngabdi, 2019)
National Energy Policy, is to increase energy diversification through efforts to use renewable energy such as renewable non-fossil fuels, especially wind energy until 2025. By utilizing renewable energy, the dependence on fossil fuels on the national energy supply system can decrease. Sumbawa Island has the potential for wind energy around 220 KW (assuming each location is built 10 units)